Effect of Different Calcination Temperatures on the Structural and Photocatalytic Performance of Bi-TiO2/SBA-15 - Jing Ma; Jia Chu; Liangsheng Qiang; Juanqin Xue (International Journal of Photoenergy)
The new novel material Bi-TiO2/SBA-15 was synthesized by an easy wet impregnation method. A combination of XRD, XPS, Raman, N2 adsorption-desorption isotherm measurement, TEM, and solid state UV-Vis spectroscopy has been used to characterize the Bi-TiO2/SBA-15 material. It was found that SBA-15 retained the ordered hexagonal mesostructure after incorporation of TiO2 and Bi. The photodecomposition of rhodamine B (RhB) in aqueous medium was selected to evaluate the photocatalytic performance of Bi-TiO2/SBA-15 under visible light irradiation (λ≥420 nm). The experiment results indicated that Bi-TiO2/SBA-15 exhibited higher photocatalytic activities than pure TiO2 and Bi2O3. The influences of calcination temperature were studied. It strongly influenced the activity of the samples. The sample calcined at 550°C shows the highest photocatalytic activity in the decomposition of RhB under visible light. The catalyst preserved almost its initial photocatalytic activity after six reuses.